THE EFFECT OF EXCHANGE RATE MISALIGNMENT ON AGRICULTURAL TRADE - 조규대 (한국농촌경제연구원, 2005)
This paper examines whether exchange rate misalignment negatively affects agricultural trade, compared to other industrial sectors. Nominal exchange rate misalignment is obtained from the percentage deviation of real exchange rates from their long-run equilibrium based on the theory of purchasing power parity. In order to explore this issue, a bilateral trade matrix involving trade flows between ten developed countries is constructed. Using panel data analysis, a gravity model is estimated for four industrial sectors over the period from 1976 to 1999. The study has found that over-valuation (under-valuation) of the nominal exchange rate negatively (positively) affects export performance of the agricultural sector in particular. In the large-scale manufacturing sectors considered in this paper, exports are not significantly affected by exchange rate misalignment.
Keywords: Exchange rate misalignment; agricultural trade; and gravity model.; Exchange rate misalignment; agricultural trade; and gravity model.